Challenges in development of vaccines directed toward antimicrobial resistant bacterial species - Michela Brazzoli; Diego Piccioli; Federico Marchetti (Taylor & Francis Group, 2023)
Antimicrobial resistance (AMR) is considered by WHO one of the top ten public health threats. New control strategies involving concerted actions of both public and private sectors need to be developed. Vaccines play a major role in controlling the spread of AMR pathogens by decreasing transmission and limiting the use of antibiotics, reducing at the end the selective pressure for the emergence of new resistant strains. In this review, by using as example some of the most serious AMR pathogens, we highlighted the major hurdles from a research and development point of view. New approaches to better understand the immunological mechanisms of response to both natural infections and vaccines that aimed to identify correlates of protection, together with the application of new technologies for vaccine design and delivery are discussed as potential solutions.